ANALYSIS OF EMPLOYEE EMPOWERMENT IN PT. BANK SULUTGO MANADO USING IMPORTANCE AND PERFORMANCE ANALYSIS - Waworuntu, Priskila Charity; Lambey, Linda .; Tielung, Maria V.J (Universitas Sam Ratulangi, 2017)
Abstract: This research aims to analyzing the employee empowerment in Main Branch of PT. Bank SulutGo Manado. This research type is descriptive with quantitative method, using Importance and Performance Analysis as analytical tool. The sample size of this research is 84 employees as respondents. Purposive sampling was used to collecting data through questionnaire. The result shows that Assistance/help by managers when face barriers in work, Encourage and motivation in work, Clear direction in completing the job, and Evaluation given by manager these attribute are located in Quadrant II. Facilities provided by Bank SulutGo in supporting the work and Supervision and control for purpose to reach the target in work are placed in Quadrant I. Meanwhile, Freedom in organizing their respective jobs are placed in low priority which is Quadrant III. And for the last there are Autonomy (freedom) in completing the work by employees’ own way and Freedom in giving opinion are placed in Quadrant IV. Main Branch of Bank SulutGo Manado should put more attention to Facilities provided by Bank SulutGo in supporting the work and Supervision and control for purpose to reach the target in work because the employees considered these attributes is important. Keywords: employee empowerment, importance and performance analysis